3+3x3-3+3=

in Algebra 1 Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

17 Answers

a problem on order of operations:

3  +  3  x  3  -  3  +  3

3    +    9    -  3  +  3

             12  -  3  +  3   =   9  +  3   =   12

by Level 4 User (5.6k points)
Should be read as 3+(3x3)-(3+3)=6
by
the answer is 3

Basic maths..

(3+3)x(3-3)+3= 3

3+3= 6

3-3= 0

6x0= 0

0+3= 3!
by
No parenthesis or exponents so multiply and divide left to right first

3+3x3-3+3 = 3+9-3+3

Then add and subtract left to right

3+9-3+9 = 12
by
3+3x3-3+3=
by
~~3+3x3-3+3=

6 x3=18-3=15+3=18
by
3+(3x3)-3+3 = 3+9-3+3 = 12-3+3 = 9+3 = 12 PEMDAS. when there is a multiplication symbol, the parenthesis are assumed automatically. even IF you left them out, you would multiply FIRST, then add/subtract left to right like normal.
by
12   3x3=9   9+3-3+3=12
by
3+3*3-3+3=6

P there ae no parentheses

E there are no exponents

M 3+9-3+3

D there is no division

A do all of the addition (3+9)-(3+3) becomes 12-6

S do all subtraction 12-6= 6
by
3+3=6X3=18-3=15+3=18 The answer is 18
by
P - N/A

E - N/A

M - (3x3) = 9

D - N/A

A - 3+(9)+3 = 15

S - 15-3 = 12

Answer = 12

Any other solution is performing PEMDAS incorrectly.
by
(3+3)=6x3=18-(3+3)=6 so its 18-6=12
by

I have another question.

Why does everyone say that 3+3x3-3+3 equals to 12 or 18 when clearly, it's not the answer.

If you need to know what the answer is, you need to follow 'PEMDAS'.

----------------

PEMDAS:

  1. P=Parentheses
  2. E=Exponents
  3. M=Multiplication
  4. D=Division
  5. A=Addition
  6. S=Subtraction

----------------

  1. 3+3x3-3+3 (Multiplication starts first) 3x3=9
  2. 3+9-3+3 (Then add both addition sentences) 3+9=12 and 3+3=6
  3. 12-6 (Lastly, we subtract) 12-6=6 since 6x2=12

That's how to find the answer to the equation: 3+3x3-3+3=6

by
reshown by
The correct answer is 6.

Parenthesis=none

Exponents=none

Multiplication= 3+(3x3)-3+3 = 3+(9)-3+3

Division =none

Addition= (3+9)-(3+3) = 12-6

Subtraction= 12-6=6........all day long!
by Level 1 User (140 points)
((3+(3x3))-3)+3=12
by
3+3X3+3  3+9+3=15
by

The answer is C.

by

Related questions

1 answer
asked May 10 in Algebra 1 Answers by Elaine Oxford | 44 views
1 answer
asked Nov 17, 2014 in Other Math Topics by papoace | 231 views
1 answer
asked Nov 6, 2013 in Algebra 2 Answers by anonymous | 99 views
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
84,404 questions
89,215 answers
1,988 comments
7,492 users